Peran Keluarga dalam Meningkatkan Nilai Moral Anak Usia Dini - Arini Ainun Ridho (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
Children are the next generation, as the next generation both for the nation and family, children need to get an education that can develop their potential. Not only good education, character and character and moral values also determine national development. There are several levels of moral development according to Kohlberg. The most important influence in the family environment is the role of parents about how the family functions and parenting that parents do to children.